Novel Supreme Drug-Eluting Stents With Early Synchronized Antiproliferative Drug Delivery to Inhibit Smooth Muscle Cell Proliferation After Drug-Eluting Stents Implantation in Coronary Artery Disease: Results of the PIONEER III Randomized Clinical Trial. Issue 22 (6th April 2021) - Lansky, Alexandra J.; Kereiakes, Dean J.; Baumbach, Andreas; Windecker, Stephan; Hussain, Yasin; Pietras, Cody; Dressler, Ovidiu; Issever, Ozgu; Curtis, Michael; Bertolet, Barry; Zidar, James P.; Smits, Pieter C.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Accelerated endothelial healing after targeted antiproliferative drug delivery may limit the long-term inflammatory response of drug-eluting stents (DESs). The novel Supreme DES is designed to synchronize early drug delivery within 4 to 6 weeks of implantation, leaving behind a prohealing permanent base layer. Whether the Supreme DES is safe and effective in the short term and can improve long-term clinical outcomes is not known. Methods: In an international, 2:1 randomized, single-blind trial, we compared treatment with Supreme DES to durable polymer everolimus-eluting stents (DP-EES) in patients with acute and chronic coronary syndromes. The primary end point was target lesion failure—a composite of cardiac death, target vessel myocardial infarction, or clinically driven target lesion revascularization. The trial was designed to demonstrate noninferiority (margin of 3.58%) of the Supreme DES at 12 months compared with DP-EES (URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03168776). Results: From October 2017 to July 2019, a total of 1629 patients were randomly assigned (2:1) to the Supreme DES (N=1086) or DP-EES (N=543). At 12 months, target lesion failure occurred in 57 of 1057 patients (5.4%) in the Supreme DES group and in 27 of 532 patients (5.1%) in the DP-EES group (absolute risk difference, 0.32% [95% CI, −1.87 to 2.5]; P non inferiority =0.002]. There were no significant differences in rates of device success, clinically driven target lesion revascularization, or stent thrombosis at 12 months, and the safety composite of cardiovascular death and target vessel myocardial infarction was 3.5% versus 4.6% (hazard ratio, 0.76 [95% CI, 0.46–1.25]) with Supreme DES compared with DP-EES, although rates of combined clinically and non–clinically driven target lesion revascularization at 12 months were higher with Supreme DES. Conclusions: Among patients with acute and chronic coronary syndromes undergoing percutaneous coronary intervention, the Supreme DES proved to be noninferior to the standard DP-EES. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03168776.